Post-Reformation Reformed sources and children - Neele, A. C. (HTS teologiese studies, 2008)
This article suggests that the topic “children” received considerable attention in the post-Reformation era – the period of CA 1565-1725. In particular, the author argues that the post-Reformation Reformed sources attest of a significant interest in the education and parenting of children. This interest not only continued, but intensified during the sixteenth-century Protestant Reformation when much thought was given to the subject matter. This article attempts to appraise the aim of post-Reformation Reformed sources on the topic “children.”